(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
In this research we will find mainly my educational history (From the traditional models, new school and constructivist. In 2010 I entered the educational institution bethel (christo-centric) studying the first grade and where years later I graduated from high school, so I delayed in 11 approximately, in 2017 everything begins to rebuild and enters the new method called active school. That is why, we are going to have as a reference guide to the pedagogical models of Julian de Zubiria Samper, where he gives different points of view and how these events have been of impact since times ago and how they are still in force today. How can pedagogical methods influence learning and the practice of knowledge from our student life? In conclusion, pedagogical models in the field of education play a fundamental role, as they are the basis to concretize different moments and allow different ways of imparting knowledge. The objective of this research was to analyze the pedagogical model in the teaching and learning process from elementary school to high school at the bethel educational institution. The data collection plan contemplates methodological strategies required by the objective and hypothesis of the research, according to the chosen approach, which for the present study is completely qualitative. this was done through a survey applied in the elementary and high school sub-levels of the bethel educational institution. In this document we will know the pedagogical methods from three different models and how they are lived from the student life where emphasis is made on different authors and how an academic research project contributes to education, giving points of view and reflective questions.